REDESIGN OF CHINESE BIDARA FLATS IN EAST JAKARTA WITH BIOPHILIC APPROACH - Hamidah, Wardah; Pratama, Fery Mulya; Dwiputri, Marselly (Universitas Indraprasta PGRI, 2024)
The Bidara Cina flats is a building constructed in 1996. The phenomenon of urbanization in Jakarta City, which caused limited land availability at that time, and the presence of numerous irregular urban areas due to the proliferation of slums, prompted the initial construction of these flats. However, the construction of this building did not immediately solve the existing problems. The lack of adequate facilities and insufficient maintenance of the building have led to an unhealthy environment. Therefore, it is hoped that the redesign of the Bidara Cina flats in the future can integrate housing function, entertainment, and provide adequate facilities. The result of this redesign is expected to become a healthy living place for the lower-middle-class community or MBR.